Configurational Lability at Tetrahedral Phosphorus: syn/anti‐Isomerization of a P‐Stereogenic Phosphiranium Cation by Intramolecular Epimerization at Phosphorus. (23rd November 2021) - Tipker, Ryan M.; Muldoon, Jake A.; Pham, Daniel H.; Varga, Balazs R.; Hughes, Russell P.; Glueck, David S.; Balaich, Gary J.; Rheingold, Arnold L.
Abstract: Tetrahedral main‐group compounds are normally configurationally stable, but P‐epimerization of the chiral phosphiranium cations syn‐ or anti‐[Mes*P(Me)CH2 CHPh][OTf] (Mes*=2, 4, 6‐(t‐Bu)3 C6 H2 ) occurred under mild conditions at 60 °C in CD2 Cl2, resulting in isomerization to give a syn‐enriched equilibrium mixture. Ion exchange with excess [NBu4 ][Δ‐TRISPHAT] (Δ‐TRISPHAT=Δ‐P(o‐C6 Cl4 O2 )3 ) followed by chromatography on silica removed [NBu4 ][OTf] and gave mixtures of syn‐ and anti‐[Mes*P(Me)CH2 CHPh][Δ‐TRISPHAT]⋅x[NBu4 ][Δ‐TRISPHAT]. NMR spectroscopy showed that isomerization proceeded with epimerization at P and retention at C. DFT calculations are consistent with a mechanism involving P‐C cleavage to yield a hyperconjugation‐stabilized carbocation, pyramidal inversion promoted by σ‐interaction of the P lone pair with the neighboring β‐carbocation, and ring closure with inversion of configuration at P. Abstract : Tetrahedral carbon and analogous four‐coordinate main‐group compounds are configurationally stable, but we report intramolecular P‐epimerization of chiral phosphiranium cations under mild conditions. How? In the proposed mechanism, P‐C cleavage yields an intermediate pendant β‐carbocation which promotes low‐barrier pyramidal inversion at phosphorus, while hyperconjugative stabilization from a P‐C σ‐bond preserves the cation's C‐chirality.